Sie sind auf Seite 1von 41

i ! : sSet dSet

Λ i [n ] X 0 i n

0 < i < n

Λ i [n ] i

0 n

X i ! (X )

X Y Hom (X, Y ) X

Y

X Y Hom (X, Y )

Y

T o

I o

T

e

v

b

f

a

w

c

d

r

a e, f, c

T

b

d

T r w

η η e e

n i [n ]

n + 1 0 , 1 , · · · , n

i [2]

i[2]:

0

1

2

T

Ω(T )

T

Ω(T ) a, b, · · · , f

r Ω(T )(b, c, d; a ) w Ω(T )(; d) v Ω(T )(e, f ; b )

1 b Ω(T )(b ; b ) r 1 v Ω(T )(e, f, c, d; a )

r · τ Ω(T )(c, b, d; a ) T

e

c

b

a

f

d

Ω(T )

r · τ r

T

T T

Ω(T ) Ω(T )

T T

X : Ω op Set

dSet

X T X T X (T )

X T X T

i [n ] n 0

i : ∆

i : dSet sSet,

sSet

i !

i : sSet dSet i !

X

i ! (X ) T =

X n , T

= i [n ] n 0

φ,

i ! : sSet dSet

P N d (P )

N d (P ) T = Hom (Ω(T ), P ),

P

Ω(S ) S N d (P )

S Ω[S ]

N d Ω(S ) = Ω[S ]

N d

X τ d (X ) X

sSet

dSet

Ω[S ] Ω[T ] = N d (Ω(S ) BV Ω(T ))

BV

Hom (X, Y ) T = Hom dSet (Ω[T ] X, Y ).

T v T T

T v e 1 e 2

v e σ v : T T

v 1 e

e

1

v

e

2

σ v

e

T v T

T/v v

Ω(T/v ) T/v

T

v : T/v T.

b

r

a

w

c

d

v

e

v

b

f

c

r

d

w

a

T v e T

e : η T

η e

T e T T/e

e

e

: Ω(T/e ) Ω(T )

T/e

e

Ω(T )

e : T/e T

e

f

u

w

c

d

a

b

e

v

f

b

c

d

w

a

r

T T T T

Ω(T ) Ω(T ) T = T C n

n

e 1 , · · · ,e n

e

1

e

2

···

e

n

ϕ Σ n C n

T |T | T

T f T f =

δϕσ δ ϕ σ

X

X = −→ lim Ω[T ]

x X T T

T α T

x = α (x ) x X T α

T T α

X Sk n (X ) X

x X T |T | ≤ n

X

Sk 0 (X ) Sk 1 (X ) Sk 2 (X ) ⊆ · · ·

(1)

X

X

S

i Sk n (X ) = Sk n (i X )

i ! Sk n (S ) = Sk n (i ! S ).

 x,T ∂ Ω[T ] Sk n (X ) x,T Ω[T ] Sk n+1 (X )

(x, T )

X T n x X T

Ω[T ] Ω[T ]

X n > 0

x X T x

X i ! (X )

X P Σ N d (P ) P

N d (P )

T : T T

Ω[T ] Ω[T ]

Ω[T ]

Ω[T ]

Ω[T ],

e T

e : T/e

T

Λ e [T ]

Ω[T ] ,

e T

Λ k [n ]

∆[n ]

∆[n ]

i ! k [n ]) = Λ k [i [n ]]

i ! (∆[n ]) = Ω[i [n ]]

i ! (∆[n ]) = Ω[i [n ]].

K

T e T

K T = Hom (Ω[T ], K ) Hom e [T ],K )

T e

X

0

< k

< n

Hom (∆[n ], X )

Hom k [n ], X )

X

i ! (X )

K

i (K )

u : U

V

u : Hom (V, K ) Hom (U, K ),

u u

T

I (T )

T

A I (T ) Λ A [T ] Ω[T ]

A A = { e } Λ A [T ] = Λ e [T ]

A I (T ) Λ A [T ] Ω[T ]

n = |A| n = 1 Λ A [T ] Ω[T ]

n < k

|A| = k

e A B = A\{ e } Λ A [T ] Ω[T ]

Λ A [T ]

Λ B [T ]

Ω[T ]

Λ A [T ] Λ B [T ]

Λ B [T/e ]

Ω[T/e ]

Λ A [T ]

Λ B [T ]

Λ B [T/e ] Ω[T/e ]

Λ I [T ] Λ A [T ] A = I (T ) Λ I [T ]

Ω[T ]

Λ I [T ] Ω[T ]

T S l T

T l S

S

T

l

S

Ω[S ] Ω[T l S ] Ω[T ]

Ω[T l S ]

Ω[T ] l Ω[S ] Ω[T l S ]

T S l T

Ω[T ] l Ω[S ] Ω[T l S ]

R = T l S T = η S = η

n = |T | + |S |

T S n = 0 n = 1

T

= η

= S n = 2

Ω[T ] l Ω[S ]

Ω[R ]

2 n < k

|T | + |S | = k

Λ I [R ] Ω[R ]

Ω[T ] l Ω[S ] Ω[R ]

Ω[T ] l Ω[S ]

Λ I [R ]

Ω[R ]

Ω[T ] l Ω[S ] Λ I [R ]

v

Cl (T )

Cl (S ) T S

l S

C Cl (T )

Ω[R ]

C

Ω[(T/C ) l S ] Ω[T/C ] l Ω[S ] Ω[(T/C ) l S

C

C

Ω[T l (S/C )]

Ω[T

l (S/C )]

Cl (S ) Ω[R ]

Ω[T ] l Ω[S/C ]

C Cl ( T ) (Ω[T/C ] l Ω[S ])

C Cl ( S ) (Ω[T ] l Ω[S/C ])

Ω[T ] l Ω[S ]

C Cl ( T ) (Ω[(T/C ) l S ]) C Cl ( S ) (Ω[T l (S/C )])

Λ I [R ]

P

x N d (P ) T x : Ω[T ] N d (P )

Ω(T ) P T

Ω(T )

x T

P P

 Λ e [T ] → N d (P ) T

2

X Y

f : Sk 2 Y Sk 2 X f

ˆ

f : Y

X

f

f k

: Sk k Y

Sk k X

 k ≥ 2 y ∈ Sk k +1 (Y ) y ∈/ Sk k (Y ) y ∈ Y T T k + 1 Λ α [T ]

k 2

{ β y } β

= α β

T

Λ α [T ] Y

k Y

 f k Λ α [T ] → X X { f (β ∗ y )} β = α f k +1 (y ) ∈ X T

β

= α

β f k +1 (y ) = f (β y )

α

f (α y ) α f k +1 (y )

S S k

k 2 S

f (α y ) α f k +1 (y )

X

f k +1 : Sk k +1 (Y ) Sk k +1 (X )

ˆ

Sk k +1 (Y )

f k

k 2 f

ˆ

f : Y X f g

ˆ

f f g

T T

k

y X S

ˆ

S

S k + 1 f (y ) g (y ) X

k 2

 ˆ f = g

τ d

N d

τ d (X )

X

X X

N d (τ d (X ))

X τ d (X )

n 0 C n

n

1

n

0

0 i n

i : η C n

η i C n

f

X C n

C n n

1
f

n

0

α : C n

C n

f α (f )

α

X f, g X C n n 0

1 i n f g i f i g

H

1

f

i

n

0

1

i

i

n

0

1

g

i

n

0

id

i

i

f

g 0 f 0 g

1

n

0

0

id

0

0

1

g

n

0

f

i

g 0 i n

f

g i H : f

1

f

n

0

H

i g

X 0 i n

i X C n

1 i n

i = 0

1

i

i

n

0

σ i

1

0

i

n

1

n

0

σ 0

0

1

n

0

f

σ i (f ) f

f f

i f

X C n

f

i

g 1

i

f g i T

1

′′

i

i

i

n

0

n H fg

Λ i [T ] i

Λ i [T ] X

X

H

i

id

id

i

i

i

′′

H

id

1

f

f

′′

i

i

n

0

id

′′

i

i

1

f

′′

i

n

0

H

fg

1

id

f

i

i

n

0

1

g

i

n

0

H i i H f f f

i H fg f g

X x

H gf = i (x)

′′

i

id

1

g

i

n

0

1

f

′′

i

n

0

g f i g i f i = 0

f i g g i h 1 i n H fg

f g H gh g h T

1

′′

i

i

i

n

0

Λ i [T ] Λ i [T ] X X

H

i

id

id

i

i

i

′′

H

gh

id

1

g

′′

i

i

n

0

H

fg

1

f

id

i

i

n

0

id

′′

i

i

1

h

′′

i

n

0

1

g

i

n

0

x

H fh =

(x)

i

id

1

f

1

h

′′

i

i

n

0

′′

i

n

0

f h f

i h

i = 0

X 0 , · · · , n X C n

f g

f i g

H : f i g 1 i n 1 i < j n

 Λ i [T ]

i

j

1

i

j

n

0

Λ i [T ] X

j

H

f

H

H

i

f

i

1

f

j

j

n

id

0

i

id

1

i

j

n

f

0

i

1

i

id

f

j

n

0

H

j

f : f j f H

i f : f i f

1

i

j

n

f

0

1

i

j

n

g

0

1

i

j

n

f

0

x (x)

i

j

id

1

i

j